The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory